Flow management and its impacts on operational performance. Issue 15 (17th November 2016) - Huo, Baofeng; Gu, Minhao; Prajogo, Daniel
Abstract: Based on the organisational capability perspective and the concept of flow management, this study examines the inter-relationships between the management of five flows (human, information, decision, logistics and production flows) and their effects on operational performance. The research model was empirically tested using data from 321 Australian companies. The results show that human flow management (HFM) has a positive effect on the management of the other four flows. Further, information flow management (IFM) is positively associated with logistics flow management (LFM), whereas decision flow management (DFM) is positively associated with both production flow management (PFM) and LFM. The results also show that HFM, PFM and LFM can improve operational performance directly, whereas IFM and DFM only enhance operational performance indirectly. Our findings contribute to flow management theories and practices.